Achievement motivation and its relationship to jump pass and jump shot in handball - Abod, Zahraa Fadel; AlHaddad, Noor Hatem (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the achievement motivation among players of Al-Bish Merka Handball Club and to determine its relationship to jump pass and jump shot in handball. The researchers used the descriptive approach in the associative relations method due to its relevance to the nature of the problem. The research community was chosen in a deliberate way and consisted of 12 players of the Al-Bish Merka Handball Club. The proportion of the research sample was 100% of the original community (12 handball players). The search data was processed through the Statistical Package for the Social Sciences (SPSS). The results indicated that the team players have an achievement motivation, as the significance value of the participants’ motivation to achieve in sports compared to the test score or hypothetical value was p = 0.05. As for the relationship between the achievement motivation and passing and shooting accuracy in high jumping, our results indicated a statistically significant relationship between these variables. In conclusion, the handball players of the Al-Bish Handball Club enjoy this sport with an achievement motive. There is a positive relationship between achievement motivation and passing and shooting accuracy, which supports the need for success through shooting accuracy from jumping high to score points. We recommend paying attention to the psychological condition of the player, as it affects the motivation to perform. It is also important to study other psychological variables and know their relationship with handball skills.